Analisis Semiotika Pada Film Parasite Dalam Makna Denotasi Konotasi Dan Pesan Moral - Melisa Theodora; Nina Siti Salmaniah Siregar; Taufik Wal Hidayat (Program Studi Antropologi Sosial Pascasarjana Universitas Negeri Medan, 2022)
Semiotic Analysis on Parasite Film is the title in this study. Parasite is a film that tells about the social inequality that occurs between the lives of two families (the Park and Kim families) who have very different economies. The Park family is a very wealthy family living in large and elite housing while the Kim family is a family whose family members are unemployed poor and live in a small semibasement house at the end of the road. The conditions experienced by the Kim Family made them try to get out of their poor life by tricking the Park Family. The storyline of this film finally made the writer interested in researching this film with the aim of analyzing the semiotic meaning of denotation and connotation as well as taking moral messages that can be taken from this film where the Parasite film has a storyline that describes human life today. This study uses Roland Barthes' Semiotic Theory. The unit of analysis in this research is the film parasite, where the author takes 10 scenes that the writer will examine. The data collection technique that the writer uses is by watching the original film that is neither cut nor censored from start to finish, observing the scenes the author studies, conducting direct interviews with informants and observing the film. This study uses a descriptive research methodology with a qualitative approach. The author also tests the validity of the data by testing the credibility or trust in the data by triangulating data sources and checking the data by conducting interviews with informants directly and asking questions related to films that help research.